Flame-Retardant Mechanism and Mechanical Properties of Wet-Spun Poly(acrylonitrile-co-vinylidene chloride) Fibers with Antimony Trioxide and Zinc Hydroxystannate - Kim, Ji Su (Polymers (Basel), 2020)
To produce flame retardant poly(acrylonitrile-co-vinylidene chloride) (PANVDC) fibers with limiting oxygen index (LOI) values above 28%, flame retardants are added to fibers. Because antimony trioxide (ATO) used widely for PANVDC is suspected as a carcinogen, non-toxic zinc hydroxystannate (ZHS) could be the alternative for reduction of ATO usage. Moreover, a flame retardant efficiency of the combination of ATO with ZHS could be expected because it was reported that ATO resists flame in the gas phase, whereas ZHS reacts in the condensed phase. Therefore, this study discussed the flame retardant mechanisms of ATO and ZHS in PANVDC, and evaluated the efficiency of the combination. PANVDC fibers with ATO and ZHS in 15 phr were produced by wet spinning. When ZHS was added, a more cyclized structure was detected (e.g., 1-methylnaphthalene) through pyrolysis−gas chromatography-mass spectrometry (Py-GC/MS). As a result of SEM-EDX analysis, Sb and Cl hardly remained in char layers of PANVDC-ATO; meanwhile, Zn, Sn, and Cl remained in that of PANVDC-ZHS. This implied that SbCl(3) from reaction of ATO and HCl reacts in the gas phase, whereas ZnCl(2) and SnCl(2) from ZHS and HCl promotes the cyclization reaction of PANVDC in the condensed phase. The LOI values of PANVDC, PANVDC-ATO, and PANVDC-ZHS were 26.4%, 29.0%, and 33.5%, respectively. This suggests that ZHS is a highly effective for PANVDC. Meanwhile, the LOI of PANVDC containing ATO-ZHS mixture is 31.0%. The combination of ATO and ZHS exhibited no efficiency. The addition of ATO and ZHS slightly reduced the tenacities of the fibers, respectively, 3.11 and 3.75 from 4.42 g/den.